Analysis of Rib Cartilages Anomalies in Patients With Microtia. Issue 4 (June 2016) - Yang, MeiRong; Jiang, Haiyue; Chen, Weiwei; Li, Qingsong; Zhang, Ye; Li, Chuan; Pan, Bo
Abstract : Objective: The objective of this study was to identify the characteristics and incidence of rib cartilages anomalies in patients with microtia and to investigate the interaction between microtia and rib cartilages anomalies. Methods: A total of 214 consecutive patients received a preoperative 3-dimensional chest computed tomography. A retrospective study was performed with the clinical and imaging data from November 2014 to July 2015. Pearson X2 test and Spearman analysis were used to analyze the interaction between microtia and rib cartilages anomalies. Results: With the 3-dimensional chest computed tomography images, a total of 62 patients (29.0%) were documented with rib cartilages anomalies including 4 patients (1.9%) with numerical variations, 13 patients (6.1%) with structural changes, and 51 patients (23.8%) with abnormal articulations. The incidence of rib anomalies ( P  = 0.035) varied with grades of microtia. Conclusions: The incidence of rib cartilages anomalies was high in patients with microtia. The authors observed a higher incidence of costal cartilages anomalies in patients with a more serious grade of microtia. Microtia with rib cartilages anomalies may involve a new syndrome previously undiscovered or just another extension with the very wide spectrum of microtia.